CHARACTERISTICS ASSESSMENT OF THE REDUNTANT RADIO SYSTEMS FOR FLIGHTS WITH TWO TYPES OF FAILURES - V. E. Emelyanov; A. P. Cruglov (Научный вестник МГТУ ГА, 2016)
The work presents the assessment of the recovery process of radio equipment for flights with two types of failures in the description of the recovery process by using the properties of the injected semi-Marcov random process. The relations for the average time for systems failure in case of their reservation, which allows to calculate the value of probability of stable states were obtained.